Bobsleigh start interval times and three-dimensional motion analysis of the lower limb joints in preparation for the 2018 Pyeongchang Winter Olympics - Park, S.; Lee, K.; Kim, D.; Yoo, J.; Jung, J.; Park, K.; Park, S.; Kim, J. (ISBS Proceedings Archive (Michigan), 2017)
This study aimed to provide data to improve the technique of Korean bobsledders. To this end, we measured the start interval times of bobsledders with different performance levels and performed a motion analysis of the lower limb joints during the start interval. We divided 12 Korean bobsledders into a superior group and an inferior group before measuring the interval times and performing the motion analysis of the lower limb joints at the start of the bobsleigh. The start interval times showed a statistically significant difference between the superior and inferior groups (p < .05). The motion analysis of the lower limb joints revealed significant differences in hip flexion and extension, and in ankle dorsiflexion, plantar flexion, and supination (p < .05). Based on these differences, we deduced that the superior bobsledders achieved superior start times by using movements that focus more on horizontal changes in the center of gravity than on vertical changes, and movements that facilitate a longer stride.